En bloc preparation of Drosophila brains enables high-throughput FIB-SEM connectomics - Lu, Zhiyuan; Xu, C S.; Hayworth, Kenneth J.; Pang, Song; Plaza, Stephen M.; Scheffer, Louis K.; Rubin, Gerald M.; Hess, Harald F.; Rivlin, Patricia K.; Meinertzhagen, Ian A. (Frontiers in Neural Circuits, 2022)
Deriving the detailed synaptic connections of an entire nervous system is the unrealized goal of the nascent field of connectomics. For the fruit fly Drosophila, in particular, we need to dissect the brain, connectives, and ventral nerve cord as a single continuous unit, fix and stain it, and undertake automated segmentation of neuron membranes. To achieve this, we designed a protocol using progressive lowering of temperature dehydration (PLT), a technique routinely used to preserve cellular structure and antigenicity. We combined PLT with low temperature en bloc staining (LTS) and recover fixed neurons as round profiles with darkly stained synapses, suitable for machine segmentation and automatic synapse detection. Here we report three different PLT-LTS methods designed to meet the requirements for FIB-SEM imaging of the Drosophila brain. These requirements include: good preservation of ultrastructural detail, high level of en bloc staining, artifact-free microdissection, and smooth hot-knife cutting to reduce the brain to dimensions suited to FIB-SEM. In addition to PLT-LTS, we designed a jig to microdissect and pre-fix the fly’s delicate brain and central nervous system. Collectively these methods optimize morphological preservation, allow us to image the brain usually at 8nm per voxel, and simultaneously speed the formerly slow rate of FIB-SEM imaging.